https://doi.org/10.36873/ PENGENDALIAN PENYAKIT ANTRAKNOSA PADA BUAH PEPAYA MELALUI COATING METABOLIT SEKUNDER TRICHODERMA : Controlling The Anthracnose On Papaya Fruits By The Coating Treatment Using Secondary Metabolites Trichoderma sp. - Rahmawati Budi Mulyani; Erina Riak Asie; C.C. Aruan (Fakultas Pertanian Universitas Palangka Raya, 2021)
The purpose of this study was to determine the effect of secondary metabolites Trichoderma longibrachiatum and Trichoderma viride to control anthracnose (Colletotrichum gloeosporioides) on postharvest papaya fruit. Phase I, in vitro experiment was performed with the variables as follows, M0 treatment: without secondary metabolites; M2: secondary metabolites of Trichoderma longibrachiatum; M3: secondary metabolites of Trichoderma viride. Phase II, in vivo testing was carried out on secondary metabolites with the best inhibition results during the Phase I, i.e. MT0: without secondary metabolites and without pathogens; MT1 : without secondary metabolites and was added with the pathogen; and MT2: secondary metabolites Trichoderma sp. and the pathogens. The in vitro test results showed that the secondary metabolites T. longibrachiatum produced the best zone of inhibition at 30.47 mm which was categorized as very strong. Secondary metabolites might affect the morphology of pathogenic hyphae such as twisted, lysis, shrinking or shrinking and swelling. In the in vivo test, there was no difference in the incubation period of the pathogen in all treatments, such as the early signs were observed on the 5th day. The lowest diameter of fruit damage was 1.93 mm in the secondary metabolites treatment of T. longibrachiatum (MT2) with only a 16.66% of disease severity compared to the group samples without secondary metabolites (MT1), which had the highest disease severity of 51.6%. Coating with secondary metabolites of T. longibrachiatum was able to extend the shelf life of papaya fruit to 8.33 days compared to the control only 6.73 days.